2000
DOI: 10.1016/s0925-4773(00)00314-2
|View full text |Cite
|
Sign up to set email alerts
|

Cactin, a conserved protein that interacts with the Drosophila IκB protein Cactus and modulates its function

Abstract: Rel transcription factors function in flies and vertebrates in immunity and development. Although Rel proteins regulate diverse processes, the control of their function is conserved. In a two-hybrid screen for additional components of the pathway using the Drosophila I-kappaB protein Cactus as a bait, we isolated a novel coiled-coil protein with N-terminal Arg-Asp (RD)- like motifs that we call Cactin. Like the other components of this pathway, Cactin is evolutionarily conserved. Over-expression of cactin in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 48 publications
5
55
0
1
Order By: Relevance
“…In addition over-expression of I-jB kinase 1 (IKK 1), an inhibitor of zebrafish NF-jB, generates the same phenotype as observed in mIjBa morphants (Correa et al, 2005), suggesting that blocking NF-jB affects caudal mesoderm development in zebrafish. Such a developmental role for NF-jB in conjunction with our studies demonstrating that knockdown of zCactin manifests a shortened tail phenotype is consistent with the positive effect of Cactin on Dorsal signalling in Drosophila (Lin et al, 2000).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In addition over-expression of I-jB kinase 1 (IKK 1), an inhibitor of zebrafish NF-jB, generates the same phenotype as observed in mIjBa morphants (Correa et al, 2005), suggesting that blocking NF-jB affects caudal mesoderm development in zebrafish. Such a developmental role for NF-jB in conjunction with our studies demonstrating that knockdown of zCactin manifests a shortened tail phenotype is consistent with the positive effect of Cactin on Dorsal signalling in Drosophila (Lin et al, 2000).…”
supporting
confidence: 88%
“…One such molecule is Cactin. The latter was initially identified in Drosophila as a novel Cactus-interacting protein by using Cactus as bait in a yeast-two hybrid screen (Lin et al, 2000). Drosophila Cactin was shown to be maternally inherited and its over-expression furthered the Cactus mutant phenotype in Drosophila by enhancing embryonic lethality and ventralisation (Lin et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Cactin was identified as a novel protein interacting with Cactus, the Drosophila ortholog of IκBα, which is important for negative regulation of the NFκB signaling pathway [28]. It has been reported that [31][32][33]28].…”
Section: Discussionmentioning
confidence: 99%
“…Given that Drosophila Cactin interacts with Cactus, which is known as an insect ortholog of mammalian IκBα [28], and that IκBα is an important negative regulator for NFκB [29], we hypothesized that Cactin may be one of the downstream genes of NFκB and may be induced by activation of NFκB. To examine whether Cactin is induced by activation of NFκB, we investigated the mRNA expression levels of Cactin after TNFα stimulation.…”
Section: Cactin Provides a Negative Feedback Loop In The Nfκb Pathwaymentioning
confidence: 99%
“…Ψ는 소수성아미노산, X는 임의의 아미노산)에서 나타난다 (Karin, 1999;Shirane et al, 1999). 면역신호에 따라 이 serine 부 위가 인산화되면, ubiquitin 단백질에 의해 인식되고, 이를 단백 질 분해 효소에 의해 IĸB가 분해되고, 결과적으로 NFĸB가 IĸB 와의 결합에서 방출되게 된다 (Burke et al, 1999;Latimer et al, 1998;Shirane et al, 1999;Lin et al, 2000;Senftleben et al, 2001). 이와 유사하게 C 말단 부위도 인산화되어 단백질 분해효 소에 노출되게 된다 (Beg and Baldwin, 1993;Liu et al, 1997).…”
Section: 한국의 전 지역에서 이러한 저항성 개체들을 분석한 결과 L1014funclassified